Solution and intuitionistic fuzzy stability of n- dimensional quadratic functional equation: direct and fixed point methods - Arunkumar, M.; Karthikeyan, S. (International Journal of Advanced Mathematical Sciences, 2014)
In this paper, the authors established the solution in vector space and Intuitionistic Fuzzy stability of n-dimensional quadratic functional equation using direct and fixed point methods.